Kacchapa Jātaka audiovisual media: effect on children’s interest in participating in the Buddhist Sunday School - Mujiyanto Mujiyanto; Sukisno Sukisno; Eko Prasetyo (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2022)
Buddhist Sunday School is one non-formal Buddhist religious education program held in most vihāras. The Buddhist Sunday School is considered necessary for improving children's understanding of the Buddha’s teaching. Various media for learning is needed to attract their interest in participating in Buddhist Sunday School. This research aims to determine how Kacchapa Jātaka audiovisual media affects the children’s interest in participating in the Buddhist Sunday School. This study observes interest, attention, motivation source, and enthusiasm towards Buddhist Sunday School material about the Kacchapa Jātaka story in the form of audiovisual media. This is quantitative research. The population of this research is children (9-14 years old) of Buddhist Sunday School Metta Dhamma in Samirono, Getasan, Semarang. This research uses a saturation sampling technique because of the small population: less than 30 children (aged 9-14 years). Based on the result of data analysis using simple linear regression formula, the magnitude of R Square is 0.744. It means that 74.4% of children’s interest in participating in Metta Dhamma Buddhist Sunday School activity is influenced by Kacchapa Jātaka audiovisual media. The results offer insightful information for Buddhist Sunday School teachers and stakeholders to enhance the efficacy of the teaching and learning process by developing engaging learning media. Instructional implications and research suggestions are provided based on the study's results.